Evaluation of bearing capacity due to radial expansion using expanding piles - Molkaraie, Pouya (2013)
The engineering community is familiar with different techniques to improve the bearing capacity and settlement characteristics of weak cohesive soils. Preload piers or expanding piles are newly invented method for improving soft soils by means of radial compression. These piers are inserted in the soil and expanded about three times their original cross-sectional area. Due to this expansion, the surrounding soil will be radially stressed, which results in consolidation and general stiffening. The main objective of this research was to investigate improvement in the bearing capacity and settlement changes in a soft clay (Kaolinite) due to applying a preload pier. To gain this goal, soil samples of Kaolinite with undrained shear strength of 15 kPa was prepared in cubic boxes. Then two concrete piles were casted in these soil samples; first one in a cavity expanded by an expanding pile to reach 6 cm diameter and the other one casted in a bored cavity with the same diameter(without expansion). Then piles were tested by loading them until failure. Load testing of the piles yielded a load settlement graph. Based on the graph applying a preload pier improved bearing capacity of the soil up to 12 percent. Settlement of the pile decreased by 11 percent